2013
DOI: 10.1021/ja404578u
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and First Total Synthesis of PM050489 and PM060184, Two New Marine Anticancer Compounds

Abstract: Microtubules continue to be one of the most successful anticancer drug targets and a favorite hit for many naturally occurring molecules. While two of the most successful representative agents in clinical use, the taxanes and the vinca alkaloids, come from terrestrial sources, the sea has also proven to be a rich source of new tubulin-binding molecules. We describe herein the first isolation, structural elucidation and total synthesis of two totally new polyketides isolated from the Madagascan sponge Lithoploc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
70
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 32 publications
0
70
0
2
Order By: Relevance
“…It has been previously suggested that the structurally distinct MDAs maytansine (9, 11) and PM060184 (13,14) (Fig. 1A) share a common tubulin-binding site with rhizoxin (9,13,14); however, both drugs were also reported to interfere with the binding of vinblastine (9,(14)(15)(16).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…It has been previously suggested that the structurally distinct MDAs maytansine (9, 11) and PM060184 (13,14) (Fig. 1A) share a common tubulin-binding site with rhizoxin (9,13,14); however, both drugs were also reported to interfere with the binding of vinblastine (9,(14)(15)(16).…”
Section: Resultsmentioning
confidence: 96%
“…1A) share a common tubulin-binding site with rhizoxin (9,13,14); however, both drugs were also reported to interfere with the binding of vinblastine (9,(14)(15)(16). To clarify the exact binding site of maytansine and PM060184 on tubulin and their mode of interaction with the protein, we solved tubulin structures in complex with either drug at 2.1-and 2.0-Å resolution, respectively, using the same experimental approach as for rhizoxin F (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations